Serotonin (5-HT) Precursor Loading with 5-Hydroxy-L-tryptophan (5-HTP) Reduces Locomotor Activation Produced by (+)-Amphetamine in the Rat - Baumann, Michael H. (2010)
BACKGROUND: Evidence suggests that increases in synaptic serotonin (5-HT) can reduce the stimulant properties of amphetamine-type drugs. Here we tested the hypothesis that administration of the 5-HT precursor 5-hydroxy-L-tryptophan (5-HTP), along with the peripheral decarboxylase inhibitor benserazide, would decrease locomotor effects of (+)-amphetamine. METHODS: Drug treatments were administered to conscious male rats undergoing in vivo microdialysis in nucleus accumbens. During dialysis sampling, rats were housed in chambers equipped with photobeams to detect forward locomotion (i.e., ambulation) and repetitive movements (i.e., stereotypy). Extracellular concentrations of dopamine (DA) and 5-HT were measured by high-pressure liquid chromatography with electrochemical detection. RESULTS: 5-HTP (10 & 30 mg/kg, i.p.) plus benserazide (30 mg/kg, i.p.) caused dose-related increases in 5-HT but failed to alter other parameters. (+)-Amphetamine (0.3 & 1.0 mg/kg, i.p.) produced dose-related increases in DA, ambulation and stereotypy. Combined administration of 5-HTP and (+)-amphetamine evoked large elevations in extracellular DA and 5-HT, but caused significantly less ambulation than (+)-amphetamine alone (~50% reduction). CONCLUSIONS: Our results confirm that 5-HTP can decrease hyperactivity produced by (+)-amphetamine, even in the presence of elevations in dialysate DA. The data suggest that 5-HTP and (+)-amphetamine may be useful to broadly enhance monoamine function in the clinical setting, while reducing undesirable effects of (+)-amphetamine.